Performance of constructed wetland technology in removal of conventional pollutants from wastewater contaminated with ibuprofen - Koh, Jiunn Kai. (2013)
This study aims to evaluate the removal efficiencies of chemical oxygen demand (COD), ammonium-nitrogen (NH4+-N) and total phosphate (TP) in tropical horizontal subsurface flow constructed wetlands (HSSF-CWs) dosed with 100μg/l of ibuprofen (IBP). The removal efficiency of each pollutant is assessed and compared between planted and unplanted bed, operating under 4 days hydraulic retention time (HRT). Results showed no significant difference in removal of COD in planted (85.3%) and unplanted (84.8%) bed. The removal of NH4+-N and TP were more efficient in planted bed (82.8% for NH4+-N and 69.4% for TP) as compared to unplanted bed (45.4% for NH4+-N and 12.6% for TP). Occasionally, negative TP removal observed in the unplanted bed was attributed to phosphate hydrolysis under anaerobic condition. The influences of IBP on the removal efficiencies of COD, NH4+-N and TP are also assessed under IBP dosages of 25μg/l and 100μg/l. At 100μg/l of IBP, significant inhibitory effect on NH4+-N and TP removal (45.4% and 12.6% respectively) was observed in the unplanted bed. The unplanted bed dosed with 25μg/l of IBP showed a better removal of NH4+-N and TP (60.3% and 41.2% respectively). By comparing between the planted beds injected with different dosages of IBP, the removal efficiencies of NH4+-N and TP improved significantly in the planted bed dosed with 100μg/l of IBP as the inhibitory effect might be extensively removed in the presence of Typha spp.. However, the inhibitory effect of IBP did not directly affect COD removal but it could be indirectly affected by the removal of NH4+-N and TP. In general, for a normal operation of a tropical HSSF-CW of this scale to treat synthetic wastewater dosed with 100μg/l of IBP, a stabilization period of approximately 28 days is required. The strong growth and the budding of new offspring of Typha spp. proved its survivability and suitability under unfavourable conditions. Furthermore, the presence of Typha spp. was able to regulate the internal environment of the wetland to favour the growth of micro-organisms, which could help in biodegradation.